Safety of tapentadol compared with other opioids in chronic pain treatment: network meta-analysis of randomized controlled and withdrawal trials. (2nd January 2021) - Freynhagen, R.; Elling, C.; Radic, T.; Sohns, M.; Liedgens, H.; James, D.; McCool, R.; Edwards, M.
Abstract: Objective: To assess the relative safety of oral tapentadol PR and other opioid analgesics for moderate or severe chronic pain in adults, we conducted a systematic review and network meta-analysis (NMA). Methods: A systematic review was conducted to identify randomized controlled trials (RCTs) and randomized withdrawal trials of tapentadol with other WHO stage II and III opioid analgesics in patients with moderate or severe chronic pain. Searches were conducted in MEDLINE, EMBASE, PubMed, Cochrane databases and trial registries. Feasibility assessment evaluated the trials' suitability for NMA. Outcomes assessed were overall AEs, overall serious adverse events, constipation, nausea, dizziness, somnolence, headache, and discontinuation due to AEs. Randomized withdrawal trials were analyzed separately to other RCTs. Results: Searches conducted in April 2019 identified 16, 604 records. Following screening and feasibility assessment, 29 RCTs and 19 randomized withdrawal trials were identified and included in the NMA. Consistent with existing research, evidence from RCTs suggested that tapentadol is associated with relatively lower odds of adverse events occurring than most active comparators. The withdrawal trial data were less clear, with higher uncertainty around the results, and results that appear to contradict the RCT evidence. There are a number of trial design factors that may be affecting these results. Conclusions: RCT evidence suggests that tapentadol can be a useful treatment option for patients suffering from chronic pain and in need of an opioid analgesic. Opioids should be prescribed by a qualified physician only after other analgesics have been considered, taking side effects and misuse risk into account.